Between phenomenological and community psychiatry: the comprehending anthropology of Jürg Zutt - Schönknecht, Peter (History of psychiatry, 2012)
Phenomenological and existential philosophical approaches to mental illness have had great influence on psychiatric research and theory in European psychiatry (Berrios, 1992: 309). Among them, the work of Jürg Zutt (1893-1980), Professor of Psychiatry at University Hospital Frankfurt 1950-63, closely relates to the anthropological psychiatry of Ludwig Binswanger, Victor von Gebsattel and Erwin Straus. Since both anthropological psychiatry and social psychiatry are based on a person-centred approach, it was hypothesized that common roots are to be detected in what is called humanistic psychology. The main finding of the present paper is that there is a strong relationship between Zutt’s concept of Comprehending Anthropology and the biopsychosocial model on which social psychiatry is based. However, it cannot be concluded from the existing evidence that the reform of psychiatric services necessarily resulted from the anthropological approach., Phenomenological and existential philosophical approaches to mental illness have had great influence on psychiatric research and theory in European psychiatry (Berrios, 1992: 309). Among them, the work of Jürg Zutt (1893-1980), Professor of Psychiatry at University Hospital Frankfurt 1950-63, closely relates to the anthropological psychiatry of Ludwig Binswanger, Victor von Gebsattel and Erwin Straus. Since both anthropological psychiatry and social psychiatry are based on a person-centred approach, it was hypothesized that common roots are to be detected in what is called humanistic psychology. The main finding of the present paper is that there is a strong relationship between Zutt’s concept of Comprehending Anthropology and the biopsychosocial model on which social psychiatry is based. However, it cannot be concluded from the existing evidence that the reform of psychiatric services necessarily resulted from the anthropological approach.